Modelling effective utilization of ICT resources and ICT capabilities in Saudi Arabia's institution of higher learning - El Hoby, Hany Mohamed Hassan Mohamed
The Ministry of Education (MOE) Saudi Arabia has always been working closely with Saudi Universities to improve the quality of institutions of higher learning. This has led to the examination on the Information and Communication Technology (ICT) capabilities for academic staff and the effective utilization of the Information and Communication Technology (ICT) resources in Saudi Arabia. To address this gap, this research, therefore, builds on the information system success model by DeLone and McLean, which is to examine the strategic links between the success of effective utilization of ICT Resources and ICT Capabilities. The study was conducted in a Kingdom of Saudi Arabia (KSA) context of institutions of higher learning. The research framework used the quantitative methodology, in line with nine main hypotheses were formulated and tested. 371 data were collected and further analyzed, which have supported all the nine main hypotheses. The following findings are established: (i) positive relationship between effective utilization of ICT Resources and ICT Capabilities of KSA higher institutions; (ii) positive relationship between ICT Resources and Management support, with Training, as well as User involvement; (iii) positive relationship between ICT Capabilities and Management support with Training, and User involvement; (iv) positive relationship between Management Support and effective utilization of ICT Resources and ICT Capabilities; (v) positive relationship between Training and effective utilization of ICT Resources and ICT Capabilities; (vi) positive relationship between User involvement and effective utilization of ICT Resources and ICT Capabilities. (vii) There is a mediating effect of Management Support, Training and user involvement between the relationship of ICT Resources/ICT Capabilities and effective utilization. The findings show the effective utilization of ICT resources and capabilities have a significant influence on education. Furthermore, the existing management support as a mediator factor which has influenced over relationships for supporting academics and improving their capabilities and continuous training programs needed on ICT resources. Several implications for the theory to evaluate the effective utilization of ICT capabilities for academics and its use, and support decision making. The major limitation of the study lies with the use of a single-informant method, cross-sectional research design and focus on any particular institutions of higher learning. In addition, the questionnaire was conducted at the end of the semester, which may have caused academics were unable to participate in the survey. Therefore, this thesis recommends that future research should use multiple response methods, longitudinal design and samples should cover a wide range institution of higher learning. In addition, academics should be undergoing continuous training that they needed. Furthermore, academics must continuously receive the top management's support and involvement in evaluating ICT resources. The findings also show that the new models have achieved the effectiveness of utilizing ICT resources and capabilities which are contributing to the development and improvement of academic processes. On conclusion, the management support, training, and user involvement support to decision making.